Pattern of Blood Stream Infections and their Antibiotic Susceptibility Profile in a Neonatal Intensive Care Unit of a Tertiary Care Hospital: A Current Perspective (IAHS Medical Journal, 2026)
Background: Bloodstream Infections (BSIs) are a significant cause of illness and mortality in Neonatal Intensive Care Units (NICUs) particularly among low birth weight and premature infants. The rise of multidrug-resistant organisms complicates treatment, making prompt identification and appropriate antibiotic selection essential. This study overviews BSI trends and antibiotic resistance in a tertiary care NICU. This study investigated bacterial pathogens' prevalence and antibiotic susceptibility patterns causing neonatal BSIs in a tertiary hospital in Chattogram, Bangladesh.Materials and methods: This retrospective study included data retrieved from Laboratory Information Systems (LIS) of Apollo Imperial Hospitals Ltd, Chattogram from January 2020 to January 2025.It included 312 blood samples from NICU patients (Aged 0–28 days) with suspected neonatal sepsis. Samples were cultured using a BACT/Alert system, followed by bacterial identification and antimicrobial susceptibility testing and data were analyzed using Microsoft Excel 2016. Results, shown as means and percentages, focused on the distribution of Gram-positive and Gramnegative organisms and their resistance patterns.Results: Of the 312 NICU blood cultures, 55% were from female and 45% from male patients (Ratio 1:1.23). Acinetobacter baumannii (31.65%) was the most common pathogen, followed by Pseudomonas aeruginosa (25.32%), Klebsiella pneumoniae, CoNS and Staphylococcus aureus. Multidrug-resistant Gram-negative bacteria predominated. Colistin was 100% effective against A. baumannii and K. pneumoniae, while tigecycline and ceftazidime-avibactam showed moderate activity. Resistance to cephalosporins, carbapenems and aminoglycosides was widespread. Chryseobacterium indologenes were highly resistant. Among Gram-positives, penicillin and ampicillin resistance were high, though vancomycin, teicoplanin and linezolid remained effective.Conclusion: Major causative agents of neonatal bloodstream infection were Acinetobacter spp. Multidrug resistance among these bacteria was observed in the study, which necessitate the implementation of antibiotic stewardship program to improve neonatal outcomes.IAHS Medical Journal Vol 8(1), June 2025; 44-51